Palladium nanoparticles deposited on a graphene–benzimidazole support as an efficient and recyclable catalyst for aqueous‐phase Suzuki–Miyaura coupling reaction. (20th December 2016) - Sarvestani, Mosayeb; Azadi, Roya
Abstract : Graphene oxide was functionalized with benzimidazole for palladium immobilization. The resultant graphene–benzimidazole‐supported palladium composite (G‐BI‐Pd) was characterized using infrared and Raman spectroscopies, transmission electron microscopy and energy‐dispersive X‐ray spectroscopy. G‐BI‐Pd showed excellent catalytic activity and fast reaction kinetics in the aqueous‐phase Suzuki–Miyaura reaction of aryl iodides and bromides with phenylboronic acid under relatively mild conditions (5–25 min, 80 °C). The catalyst can be used several times without any significant loss of its catalytic activity. Abstract : Graphene oxide was functionalized with benzimidazole for palladium immobilization. The resultant graphene–benzimidazole‐supported Pd composite (G‐BI‐Pd) was used for the aqueous‐phase Suzuki–Miyaura reaction of aryl iodides and bromides with phenylboronic acid under relatively mild conditions.